Experiences of community service health professionals working in rural hospitals of Limpopo Province, South Africa - Shipalana, Evans (My University, 2019)
Background: Community service health professionals working in rural areas experience challenges such poor accommodation, poor supervision, unavailability of equipment and medication. The majority of studies focussed on doctors, with a few including dentists and pharmacists. This study intended to establish the experiences of community service health professionals in all professions. Objective(s): The objectives of the study were to describe and explore the experiences of community service health professionals. Methods: A qualitative, exploratory and descriptive study was conducted. Purposive sampling was used to select community service health professionals for the study. Face to face interviews with community service health professionals were conducted to collect data. Community service health professionals were interviewed until data saturation was reached. The Tesch‘s eight steps were used to analyze data. Results: The study findings indicated that community service health professionals experienced challenges relating to accommodation, supervision and unavailability of equipment and medication. Conclusions: Community service health professionals are experiencing challenges regarding working in Limpopo province rural hospitals. It is recommended that the government should allocate more funds to health care services to address the challenges faced by community service health professionals
Thesis(MPH.) -- University of Limpopo, 2019
Keywords: Community service; Community service health professionals; Experiences and Rural hospitals; Medical personnel.; Community health services -- South Africa -- Limpopo.; Health professionals.